2004
DOI: 10.1111/j.1744-7348.2004.tb00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between water‐soluble Ca and other elements and bitter pit occurrence in ‘Idared’ apples: a multivariate approach

Abstract: SummaryThe mineral composition of sound fruits of Idared apple and those with symptoms of bitter pit was investigated at two sites on M9 rootstock (Sites 1 and 2) and two sites on MM 106 rootstock (Sites 3 and 4). Concentrations of N, P, K, Ca and Mg were measured. Mg and Ca concentration were determined in water soluble (WS) and water‐insoluble (WI) fractions. The sum of these fractions was regarded as the total concentration (T). At all four sites, Ca (WS) was significantly higher in sound fruit. Principal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 11 publications
2
7
0
2
Order By: Relevance
“…These results agree with other studies showing that high susceptibility of apple fruit to BP is associated with lower levels of water-soluble Ca 2+ in the fruit (Steenkamp et al, 1983;Pavicic et al, 2004;Amarante et al, 2013) and may explain the differences in BP susceptibility between Fuji and GS despite similar skin and flesh Ca 2+ concentrations. In this case, the water-soluble pectin fraction could also contribute to the water-soluble Ca 2+ content in the fruit tissue.…”
Section: Cell Wall Pectin and Bp Development In Fruit Tissuesupporting
confidence: 94%
“…These results agree with other studies showing that high susceptibility of apple fruit to BP is associated with lower levels of water-soluble Ca 2+ in the fruit (Steenkamp et al, 1983;Pavicic et al, 2004;Amarante et al, 2013) and may explain the differences in BP susceptibility between Fuji and GS despite similar skin and flesh Ca 2+ concentrations. In this case, the water-soluble pectin fraction could also contribute to the water-soluble Ca 2+ content in the fruit tissue.…”
Section: Cell Wall Pectin and Bp Development In Fruit Tissuesupporting
confidence: 94%
“…The link between bitter pit and low cellular concentrations of calcium in the apple cortical tissue is well documented (Amarante et al 2006, Pavicic et al 2004, Ferguson and Watkins 1989, and lower levels of calcium in the fruits has been suggested to be caused by insufficient supply of calcium to the tissues following rapid increases in the nutrient requirement during fruit development (Greene 1991), along with possible changes in xylem functionality during fruit development (Amarante et al 2013). The uptake of macronutrients, including calcium, by plants and its allocation to various subcellular compartments and tissues is performed by transport proteins (Blatt 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Apple fruits with a higher content of N have a higher concentration of ethylene and level of respiration (Fallahi et al, 2006;Sharma et al, 2012). Pavičić et al (2004) reported that the level of N in the fruit cannot be used as an indicator of bitter pit in apple cultivar 'Idaredʼ. Miqueloto et al (2011) found that fruits with symptoms of bitter pit have a higher ethylene production, respiration and titratable acidity, but lower pH, firmness, texture and Spraying with CaCl 2 during the vegetation, sometimes beginning in June, proved to be the most economically efficient measure to increase the Ca in fruit and reduce the risk of bitter pit (Peryea et al, 2007).…”
Section: Treatments With Calciummentioning
confidence: 99%
“…Some of the fractions, such as water-soluble Ca, are physiologically active and responsible for the development of bitter pit (Saks et al, 1990). Insoluble Ca fraction is bound to the cell walls and cannot play an important physiological role, while water-soluble Ca is physiologically active fraction and can change activity of the different enzymes (Pavičić et al, 2004). In bitter pit affected fruit, Ca is accumulated in the areas affected by bitter pit in surface tissue, but in unaffected fruit Ca ing rootstock, ratio of vegetative and generative growth and storage handling.…”
Section: Introductionmentioning
confidence: 99%